Reversion of cardiac dysfunction by a novel orally available calcium/calmodulin-dependent protein kinase II inhibitor, RA306, in a genetic model of dilated cardiomyopathy. Issue 2 (8th April 2019) - Beauverger, Philippe; Ozoux, Marie-Laure; Bégis, Guillaume; Glénat, Valérie; Briand, Véronique; Philippo, Marie-Claire; Daveu, Cyril; Tavares, Georges; Roy, Sébastien; Corbier, Alain; Briand, Pascale; Dorchies, Olivier; et al.
Abstract: Aims: Despite improvements in patient identification and management, heart failure (HF) remains a major public health burden and an important clinical challenge. A variety of animal and human studies have provided evidence suggesting a central role of calcium/calmodulin-dependent protein kinase II (CaMKII) in the development of pathological cardiac remodelling and HF. Here, we describe a new potent, selective, and orally available CaMKII inhibitor. Methods and results: Chemical optimization led to the identification of RA306 as a selective CaMKII inhibitor. This compound was found potent on the cardiac CaMKII isoforms delta and gamma (IC50 in the 10 nM range), with pharmacokinetic properties allowing oral administration in animal models of HF. RA306 was administered to diseased mice carrying a mutation in alpha-actin that is responsible for dilated cardiomyopathy (DCM) in humans. In two separate studies, RA306 was orally administered at 30 mg/kg either for 2 weeks (twice a day) or for 2 months (once a day). Echocardiography monitoring showed that RA306 significantly improved cardiac function (ejection fraction and cardiac output) as compared to vehicle. These disease modifying effects of RA306 were associated with inhibition of cardiac phosphorylation of phospholamban (PLN) at threonine-17, indicating reduced cardiac CaMKII activity. Conclusion: This work supports the feasibility of identifying potent orally available CaMKII inhibitors suitable for clinical use to treat heart disease.